Probing ultrafast proton induced dynamics in transparent dielectrics. (16th March 2018) - Taylor, M; Coughlan, M; Nersisyan, G; Senje, L; Jung, D; Currell, F; Riley, D; Lewis, C L S; Zepf, M; Dromey, B
Abstract: A scheme has been developed permitting the spatial and temporal characterisation of ultrafast dynamics induced by laser driven proton bursts in transparent dielectrics. Advantage is taken of the high degree of synchronicity between the proton bursts generated during laser-foil target interactions and the probing laser to provide the basis for streaking of the dynamics. Relaxation times of electrons (<10 −12 s) are measured following swift excitation across the optical band gap for various glass samples. A temporal resolution of <500 fs is achieved demonstrating that these ultrafast dynamics can be characterized on a single-shot basis.